Modeling Circadian Phototransduction: Quantitative Predictions of Psychophysical Data - Rea, Mark S.; Nagare, Rohan; Figueiro, Mariana G. (Frontiers in Neuroscience, 2021)
A revised computational model of circadian phototransduction is presented. The first step was to characterize the spectral sensitivity of the retinal circuit using suppression of the synthesis of melatonin by the pineal gland at night as the outcome measure. From the spectral sensitivity, circadian light was defined. Circadian light, thereby rectifies any spectral power distribution into a single, instantaneous photometric quantity. The second step was to characterize the circuit’s response characteristic to different amounts of circadian light from threshold to saturation. By doing so a more complete instantaneous photometric quantity representing the circadian stimulus was defined in terms of both the spectral sensitivity and the response magnitude characteristic of the circadian phototransduction circuit. To validate the model of the circadian phototransduction circuit, it was necessary to augment the model to account for different durations of the circadian stimulus and distribution of the circadian stimulus across the retina. Two simple modifications to the model accounted for the duration and distribution of continuous light exposure during the early biological night. A companion paper (https://www.frontiersin.org/articles/10.3389/fnins.2020.615305/full) provides a neurophysiological foundation for the model parameters.